PEMANTAPAN KINERJA DAN PROFESIONALISME DOSEN MELALUI PERSIAPAN SERTIFIKASI DOSEN SEKOLAH TINGGI TEOLOGI TABGHA BATAM (JURNAL BEATITUDES, 2023)
This paper aims to understand the important role of lecturer certification in improving the performance and professionalism of lecturers at the Tabgha Theological College Batam. Lecturer performance is the output of the process carried out by the lecturer through work presentations, work implementation, work achievements, work results and work performance. Lecturer certification is a relevant instrument for assessing the professionalism of lecturers in order to determine the eligibility of lecturers, protect the teaching profession as agents of learning in tertiary institutions, and improve educational processes and outcomes to support the realization of national education goals. Lecturer performance can be seen from his enthusiasm in carrying out the duties of higher education tridarma assigned to him. This research uses qualitative and quantitative approaches by collecting data through surveys, interviews, and document analysis related to preparation for lecturer certification. It is hoped that the results of this research can provide valuable insights for other higher education institutions in an effort to improve the quality and professionalism of lecturers.